PERFORMANCE ASSESSMENT USING RUBRIC TO IMPROVE STUDENTS’ SPEAKING SKILL - Titik Ismailia (JALL (Journal of Applied Linguistics and Literacy), 2021)
This paper describes the implementation of performance assessment through video on speaking ability for 67 students of an Accounting study program Politeknik Negeri Jember. The aim was to make the students able to demonstrate speaking ability in a form of video during the process of an online teaching-learning process. Constructing a performance assessment involves planning tasks, performance criteria, scoring, and evaluating. A scoring rubric was chosen for scoring and evaluating students’ videos. At the last step of evaluation, this classroom action research aired that students actively participate in the process of making the product and fulfill the criteria of speaking assessment: pronunciation, vocabulary, grammar, fluency, and task. It can be concluded that rubric in performing speaking improves the students’ performance in demonstrating the ability on speaking interactively with their partner in a video.